How much can combinations of measures reduce methane and nitrous oxide emissions from European livestock husbandry and feed cultivation?. (1st July 2021) - aan den Toorn, S.I.; Worrell, E.; van den Broek, M.A.
Abstract: In the EU28, the meat and dairy supply chains emitted 360 Mt CO2 -eq or 80% of all agricultural CH4 and N2 O emissions in 2016, which must be reduced to reach net-zero greenhouse gas emissions by 2050. Our research explores how far these emissions can be reduced by combining field tested mitigation measures for beef cattle, dairy cattle, swine, sheep, and synthetic fertilizers. Many mitigation measures targeting enteric fermentation, manure management, and fertilizer application have been experimentally tested; however, the impact of combining measures is relatively unexplored. To address this knowledge gap, we use graph theory to create combinations of measures for which we calculate the overall mitigation potential. From previous review studies, we identified 44 measures and formulated rules on impossible and mandatory combinations of measures. Based on the resulting sets of feasible cliques in the graphs and a simplified technological baseline, we estimate that the combinations with the highest reductions reduce CH4 and N2 O emissions from beef cattle by 57%, dairy cattle by 47%, swine by 70%, sheep by 48%, and synthetic fertilizers by 44%. Together, they can reduce CH4 and N2 O emissions in the EU28 from meat and dairy production by 54%, and for agriculture overall by 42%. This indicates that implementing more measures in the meat and dairy sectors can create room for further reduction than in the existing modelled pathways for the EU28. However, technical measures are incapable of fully eliminating agricultural CH4 and N2 O, so there remains a need for CO2 removal technologies. Highlights: Highest mitigating combinations reduce CH4 from EU28 meat and dairy production by 62%. Highest mitigating combinations reduce N2 O from EU28 meat and dairy production by 32%. The best combinations reduce CH4 and N2 O in CO2 -eq from meat and dairy by 54%. Implementing the best combinations reduces agricultural CH4 and N2 O in CO2 -eq by 42%.